KEGIATAN BERMAIN MATEMATIKA - SARI, RATIH PERMATA (Program Studi Magister Pendidikan Anak Usia Dini, 2013)
This study aims to describe the implementation of practices in terms of mathematicrelated playing activities, in terms of the locations, the participation of children, games being used, and the principles of early childhood mathematics instruction based on the level ofdevelopment of children, as practiced in R.A. Kartini Aisyiyah Kindergarten 21, Malang. This typeof research is a form of qualitative research case study. The results include: learning activitiesapplied by teachers using the concept of learning by playing, both indoor and outdoor, and eitherindividually or collectively. The games-augmented playing activities are designed along theconcept of jovial playful ambiance, corresponds to the developmental characteristics of childrenaged 4 -5 years. Key words: playing math, case study. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan kegiatan bermainmatematika yang meliputi lokasi, partisipasi anak, permainan yang digunakan, dan prinsip-prinsippembelajaran matematika anak usia dini berdasarkan tingkat perkembangan anak, seperti yangdilakukan di RA Kartini Aisyiyah TK 21, Malang. Jenis penelitian ini adalah penelitian kualitatifstudi kasus. Hasil penelitian meliputi: kegiatan belajar yang diterapkan oleh guru menggunakankonsep belajar dengan bermain, baik indoor maupun outdoor dan baik secara individual maupunkolektif. Kegiatan bermain game dirancang sepanjang konsep riang suasana menyenangkan, sesuaidengan karakteristik perkembangan anak usia 4 -5 tahun. Kata kunci: bermain matematika, studi kasus